2018
DOI: 10.1186/s12995-018-0209-6
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction revisited: a reappraisal of work-related olfactory dysfunction caused by chemicals

Abstract: Occupational exposure to numerous individual chemicals has been associated with olfactory dysfunction, mainly in individual case descriptions. Comprehensive epidemiological investigations into the olfactotoxic effect of working substances show that the human sense of smell may be impaired by exposure to metal compounds involving cadmium, chromium and nickel, and to formaldehyde. This conclusion is supported by the results of animal experiments. The level of evidence for a relationship between olfactory dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 135 publications
0
30
0
2
Order By: Relevance
“…Our results suggested that compared to “white collar” workers, individuals with a manufacturing background exhibited accelerated olfactory decline, independently of sex and education. Findings from previous cross-sectional studies indicate that the exposure to certain work-related chemicals may harm the olfactory system ( 29 , 30 ). Note, however, that manufacturing profession did not survive as a predictor in the multi-adjusted model.…”
Section: Discussionmentioning
confidence: 97%
“…Our results suggested that compared to “white collar” workers, individuals with a manufacturing background exhibited accelerated olfactory decline, independently of sex and education. Findings from previous cross-sectional studies indicate that the exposure to certain work-related chemicals may harm the olfactory system ( 29 , 30 ). Note, however, that manufacturing profession did not survive as a predictor in the multi-adjusted model.…”
Section: Discussionmentioning
confidence: 97%
“…6,10 We speculate that exposure to certain xenobiotics, such as an HD, induces the inflammatory state and affects the lower airway 6,10 and nasal airway function. 11 A previous study reported an association of HD usage with asthma, 1 although they did not identify a dose-response relationship; another study reported an association with small airway impairment, 6 although they only examined 24 children. Our results were similar, except that we also identified dose-response relationships and examined larger numbers of children.…”
Section: Exposure To Humidifier Disinfectants Is Associated With Upper and Lower Airway Diseasesmentioning
confidence: 99%
“…La anosmia/hiposmia puede ser manifestación de distintas patologías de base, las más frecuentes son enfermedades rinosinusales, trastornos posinfecciosos (infección respiratoria alta), y trastornos postraumáticos, otras etiologías menos frecuentes son causas congénitas, idiopáticas, tóxicos, y enfermedades neurodegenerativas 19 . Otra forma de clasificarlas son etiologías conductivas y/o traumáticas, y etiologías sensorioneurales, descritas en la Tabla 1, aunque algunas etiologías son mixtas, y en varios casos, no se ha logrado determinar la fisiopatología 15,[20][21][22][23][24][25][26] . Para una revisión de los medicamentos que puedan causar alteración del olfato, referimos al lector al artículo publicado por Susan S. Schiffman 27 .…”
Section: Patología Cuantitativaunclassified